Wisata Budaya Jawa Tengah Games As A Means Of Preserving The Culture Of Central Java - Christine Ayu Wulandari (Soegijapranata Catholic University, 2017)
Indonesia has a cultural diversity in each area, one in Central Java as the existence of a tradition of Dugderan, Semarang and Ruwatan Rambut Gimbal,Wonosobo. But the growing globalization era resulted in the mindset of the society be affected which can have an impact such as forgetting the culture itself so that it can ignore the Indonesia cultural heritage asset. The result of the neglect of cultural relics is the claim that ever happened in Indonesia as Reog Ponorogo, Wayang Kulit. See the importance of the efforts in heritage preservation then performed with a way that can be introduced and as a medium of instruction, will be a cultural heritage with the theme of cultural traditions through Central Java games mobile. Game not forever impacted negatife but can be used as an interesting learning media can be called Educational Games